Perlindungan Hukum bagi Para Pencari Kerja atas Diskriminasi Usia di Indonesia - Ramadhani Febriansyah; Femmy Silaswati Faried; Firstnandiar Glica Aini Suniaprily (Jurnal Hukum Lex Generalis, 2025)
One of the factors contributing to the increase in unemployment in Indonesia is the difficulty of meeting job qualifications, a common example being maximum age restrictions. The enactment of Article 35 (1) of the Manpower Act has led the majority of employers to arbitrarily apply qualifications, especially age restrictions as one of the qualification requirements, which greatly hinders job seekers from obtaining decent work. The presence of Article 5 of the Manpower Act should serve as a guideline for employers to apply qualifications that treat job seekers humanely and do not discriminate. Due to age discrimination against job seekers, one of the affected job seekers filed a judicial review of Article 35 (1) of the Manpower Act against Article 28D of the 1945 Constitution to the Constitutional Court so that job seekers could find legal protection. This study aims to describe the legal protection for job seekers against the discrimination they experience. This study uses a doctrinal approach, descriptive research, and secondary data in the form of several job postings on social media. Upon the submission of the judicial review petition, the judge could not position himself as a job seeker and therefore decided to reject the petition. In this case, the article in question remains in force and job seekers have not yet found legal protection.